THE INFLUENCE OF BRAND AMBASSADOR ON PURCHASE INTENTION UMRAH PACKAGE - Abu Bakar, Noor Aishah; Abu Bakar, Noorilyana; Hassan, Noor Azimah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
This study was conducted to determine the influence of brand ambassador on purchase intention umrah package. In this study, researchers recruited 366 Muslim respondents who stayed in the Klang Valley area. This study applied credibility, trustworthiness, and physical attractiveness of the brand ambassador as determinants of purchase intention. The quantitative approach has been employed, and an online questionnaire was distributed. This study employed a descriptive research design, and data analysis was conducted using SPSS version 26 software. Throughout this study, results have shown there is a significant relationship between credibility, trustworthiness, and physical attractiveness of the brand ambassador towards purchase intention umrah package.